Permanence in diversity : Netherlands ecological research on Edgeøya, Spitsbergen - Boschman, Nienke; Hacquebord, Louwrens (Circumpolar studies, 2004)
With the publication of this special issue of Circumpolar Journal, the Arctic Centre of the University of Groningen would like to honour Piet Oosterveld as the driving force behind biological research on Edgeøya, Spitsbergen. He invested large amounts of time and energy in this research and he was an inspiration for many students. The book starts with an article about Piet Oosterveld's Arctic activities written by Louwrens Hacquebord. After some fieldwork in Iceland Piet Oosterveld's Arctic career really started with a wintering spent on Edgeøya in 1968-1969. In this book Piet Oosterveld's comp.